Glaucocalyxin B Alleviates Lipopolysaccharide-Induced Parkinson’s Disease by Inhibiting TLR/NF-κB and Activating Nrf2/HO-1 Pathway - Wei Xu; Deyu Zheng; Yuanyuan Liu; Ji Li; Li Yang; Xiuli Shang (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Parkinson’s disease (PD) is a common neurodegenerative disease in the old population, characterized by dopaminergic neuron loss, inflammation and oxidative stress injury in the substantia nigra. Glaucocalyxin B (GLB), an ent-kauranoid diterpenoid isolated from Rabdosia japonica, has anti-inflammation and anti-tumor effects. However, its effects on PD remain unclear. Methods: PD was introduced in rats via injection of lipopolysaccharide (LPS) into cerebral corpus striatum, and GLB was given intracerebroventricularly to these rats. Their walking, climbing and sensory states were detected by Stepping, Whisker and Cylinder Tests. The expression of tyrosine hydroxylase (TH), glial fibrillary acidic protein (GFAP), CD11b and ionized calcium binding adaptor molecule (IBA)-1 were detected by immunohischemical staining. The levels of a series of inflammatory factors, oxidative stress-related factors and apoptosis-related factors were measured by real-time PCR, immunoblotting and ELISA. In addition, Toll-like receptor (TLR)/nuclear factor kappa B (NF-κB) and nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase (HO)-1 pathways were investigated to illustrate the underlying mechanism. In vitro, microglial cells exposed to LPS were treated with GLB. Results: The injection of LPS caused walking, climbing and sensory disturbances in rats, induced inflammation, oxidative stress response and apoptosis, and activated TLR/NF-κB and Nrf2/ HO-1 pathways in the cerebral tissue. GLB administration attenuated LPS-induced alterations. The TLR/NF-κB pathway was deactivated and Nrf2/HO-1 was activated after application of GLB. In vitro, cytotoxic effects induced by the conditioned medium derived from microglial cells exposed to LPS in PC12 cells were attenuated by GLB. Conclusion: GLB suppresses LPS-induced PD symptoms by modification of TLR/NF-κB and Nrf2/HO-1 pathways in vivo and in vitro.